Diksi dan Gaya Bahasa dalam Puisi-puisi Facebook Karya Tarsy Asmat Seri Sayap-Sayap Pembebasan - Yohanes Servulus Krisnal Baruk (Medan Resource Center, 2021)
A literary work is an expression of experience, an emotional outpouring of human souls, feelings and thoughts expressed in the form of a work in the form of poetry, or other literary genres. Stylistics part of the diction is related to individual expressions or characteristics that have a high artistic value. With language style we can judge the person, disposition and abilities of a person who uses language. Then it can be said that diction and stylistics are the foundation for an author to produce beautiful poems. The problem in this study is how the use of diction and language style in ten collections of facebook poems by Tarsy Asmat series liberation wings. The result obtained from this study is the use of several types of diction with a total of 50 data, which includes: (1) the connotation of 23 data (2) denotation 4 data. (3) common words 1 data, (4) special words 7 data, (5) abstract words 3 data, and (6) use indria 12 data. (As for the language style, there are 55 data which include: (1) personification style 24 data, (2) hyperbolic style 8 data, (3) metaphorical language style 8 data, (4) climax language style 5 data (5) repetition language style 3 data, (6) simile language style 5 data, (7) paradoxical language style 1 data, (8) sarcasm language style 1 data. With this research, it is hoped that it can increase knowledge for literary lovers about the extent of the role of diction and the style of language to produce a beautiful literary work of poetry. Because diction and stylistics are part of the element of beauty in literature.